Microbiological assessment of technogenicaly disturbed forest ecosystems in Central Siberia - A. V. Bogorodskaya (Сибирский лесной журнал, 2016)
The state of soil microbial complexes of forest ecosystems of Central Siberia, disturbed by cutting, fires, emissions of pollutants and mining was investigated. The most appropriate indicators for early diagnosis of the condition and sustainability assessment of soils were the contents of microbial biomass, the intensity of the basal respiration and microbial metabolic quotient. Recorded time quantitative and structural-taxonomic restructuring of ecological trophic groups of microorganisms exhibited orientation of the elementary soil-biological processes and allowed detail to assess the state of soils of disturbed forest ecosystems. Successions of soil microorganisms reflected stages of plant succession after cutting. Structural and functional changes in the microbial soil complexes marked by only one-two years after cutting of coniferous forests. For the grassy stage in deciduous young stands, there was an increase in soil microbial activity that accompanied the development of the sod process. Microbiological processes were balanced and comparable to the control at the stage of closed 30-year-old stands. Post-fire recovery of the microbial soil complexes was determined by fire severity and by the properties of soils and vegetation succession. Functional activity of microbial soil complexes were recovered in one or two years after a low-intensity fires, whereas after high-intensity fires – was not recovered in eight years. Indicative responses of soil microorganisms in the sustainable impact of aggressive pollutants tundra zone of the Norilsk industrial region were registered at the functional and at the structural level. In areas of moderate and weak disturbances of vegetation, there were quantitative changes, whereas strong disturbances and constant exposure to pollutants marked structural and taxonomic adjustment of microbial soil complexes, disturbed dynamic processes of synthesis-mineralization and reduced adaptive capacity saprophytic microorganisms as to the existence of low temperatures, and to the effects of pollutants. Successional development microorganisms of dumps of different ages defined as properties of soils, surface slope, and the development of vegetation. Reclamation of dumps with the application of topsoil accelerated the development of meadow vegetation and succession microbial complexes.